2019
DOI: 10.1098/rspa.2019.0544
|View full text |Cite
|
Sign up to set email alerts
|

Location of eigenmodes of Euler–Bernoulli beam model under fully non-dissipative boundary conditions

Abstract: The Euler–Bernoulli beam model with non-conservative feedback-type boundary conditions is investigated. Components of the two-dimensional input vector are shear and moment at the right end, and components of the observation vector are time derivative of displacement and slope at the right end. The boundary matrix containing four control parameters relates input and observation. The following results are presented: (i) if one and only one of the control parameters is positive and the rest of them are equal to z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…A numerical scheme that preserves the exponential stability of the original continuous Euler-Bernoulli model with a clamped end and boundary control is proposed in [5] without introducing additional numerical viscosity. The Euler-Bernoulli beam with one clamped end is considered in [6] as a control system with two-dimensional input and output. It is shown that the spectrum of the generator is located in the open upper half-plane for the considered model, and asymptotic approximations of the eigenvalues are proposed.…”
Section: Introductionmentioning
confidence: 99%
“…A numerical scheme that preserves the exponential stability of the original continuous Euler-Bernoulli model with a clamped end and boundary control is proposed in [5] without introducing additional numerical viscosity. The Euler-Bernoulli beam with one clamped end is considered in [6] as a control system with two-dimensional input and output. It is shown that the spectrum of the generator is located in the open upper half-plane for the considered model, and asymptotic approximations of the eigenvalues are proposed.…”
Section: Introductionmentioning
confidence: 99%